Empowerment of wirid group (study of mothers) through fish nugget processing utilizing fish potential in Haranggaol Sub-District Haranggaol Horison District, Simalungun Regency - Ritonga, Fajar Utama; Thamrin, Husni; Suriadi, Agus; Berlianti (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2019)
Great potential as a producer of Goldfish and Tilapia in the Haranggaol Village is very large, and the production of fish is very well known up to the city of Medan, each Goldfish buyer knows the quality of Goldfish originating from the Haranggaol Region and has a relatively high price (above average) (average price of goldfish from other regions), but the fish production can be developed further from economic value if obtained in other forms such as fish processing into fish nuggets which are still rarely carried out by the local community, by looking at the potential quantity and quality of fish in Haranggaol Village. used as a potential source of Social Welfare for the community, especially the wamad mamak (recitation of mothers) group who routinely conduct recitation in the Haranggaol Village.